Licoricidin combats gastric cancer by targeting the ICMT/Ras pathway in vitro and in vivo - Ma, Hanwei; Wu, Fahong; Bai, Yinliang; Wang, Tianwei; Ma, Shangxian; Guo, Liuqing; Liu, Guiyuan; Leng, Guangxian; Kong, Yin; Zhang, Youcheng (Frontiers in Pharmacology, 2022)
Licoricidin, a type of isoflavonoid, is extracted from the root of Glycyrrhiza glabra. It has been widely proven that licoricidin possesses multiple biological activities, including anti-cancer effects and a powerful antimicrobial effect against Helicobacter pylori (H. pylori). However, the exact mechanism of licoricidin against gastric cancer remains unclear. In this study, we comprehensively explored the effects of licoricidin on MGC-803 gastric cancer cells in vitro and in vivo and further elucidated its mechanism of action. Our results revealed that licoricidin exhibited multiple anti-gastric cancer activities, including suppressing proliferation, inducing apoptosis, arresting the cell cycle in G0/G1 phase, and inhibiting the migration and invasion abilities of MGC-803 gastric cancer cells. In addition to this, a total of 5861 proteins were identified by quantitative proteomics research strategy of TMT labeling, of which 19 differential proteins (two upregulated and 17 downregulated) were screened out. Combining bioinformatics analyses and the reported roles in cancer progression of the 19 proteins, we speculated that isoprenyl carboxyl methyltransferase (ICMT) was the most likely target of licoricidin. Western blot assays and IHC assays subsequently proved that licoricidin significantly downregulated the expression of ICMT, both in MGC-803 cells and in xenograft tumors. Moreover, licoricidin effectively reduced the level of active Ras-GTP and blocked the phosphorylation of Raf and Erk, which may be involved in its anti-gastric cancer effects. In summary, we first demonstrated that licoricidin exerted favorable anti-gastric cancer activities via the ICMT/Ras pathway, which suggests that licoricidin, as a natural product, could be a novel candidate for the management of gastric cancer.